A STUDY OF THE LIGHT EMISSION FROM SiNx FILMS - Anstey, Jordan (My University, 2011)
The use of silicon in optoelectronics is gaining interest due to the possibility of applications such as optical interconnects. Though much progress has been made, the search still continues for the elusive silicon light emitter, which could make the prospect of silicon photonics a reality. This work has examined the properties of a potential candidate for a silicon-based light source: silicon nanocluster embedded silicon nitride films. In addition, the optical properties of Ce-doped silicon nitride films with and without nanoclusters were investigated.
The silicon nitride films exhibited bright luminescence that peaked after annealing at temperatures between 600oC and 800oC, depending on how the nitrogen was introduced during the deposition; the more silicon rich films (for which a dispersion ring was used) peaked at a lower anneal temperature. As well, the photoluminescence (PL) spectra of the plasma and dispersion ring samples had main peaks at about 650 nm and 750 nm, respectively. Lastly, all the spectra exhibited a redshift at higher anneal temperatures. These observations support the opinion that silicon nanoclusters were formed from the excess silicon. However, TEM imaging did not show conclusive evidence of their existence.
The Ce-doped films displayed even brighter luminescence. When the cerium was implanted into stoichiometric silicon nitride the emission was solely from Ce3+ ions, with the PL spectra being centred at 450 nm. However, when the cerium was implanted into the silicon rich film, there appears to be emission from both Ce3+ ions and silicon nanoclusters as the broad PL spectrum ranges from about 450 nm to 750 nm. After annealing at 1000oC there is a shift in the PL spectrum and the emission is almost exclusively from Ce3+ ions. Both films exhibited a strong increase in PL intensity with annealing above 1000oC, but it is not known if this is due to the formation of cerium silicate, which has been suggested before with Ce-doped silicon oxide films.